Aportes del diseño industrial con el fin de potenciar el turismo en Colombia : caso de estudio: Makuruma-Palomino (2020)
The Makuruma - Palomino project is a hosting service model that links the Industrial Design and the tourism sector through its implementation in three modalities: hostel which is an economic type of lodging in which services are offered additional services such as a common kitchen or volunteering, where you provide a service in exchange for your stay. glamping that is based on the camping modality but in a much more comfortable and sophisticated and Indigenous reserve, which is a modality raised since the development of the project where native representatives of indigenous communities and tourist visitors They interact through the word and work of said culture; Each with a location strategic within the territory